Green waste management methods in educational institutions: a systematic review focused in sustainability - Pandini, Danieli Ribeiro; Freitas, Yasmin Coelho de; Korres, Adriana Marcia Nicolau (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
The proper management of solid waste and sustainable alternatives of treatment are trends that affect all levels of society, including educational institutions (EI). This study addresses a systematic review of the literature available on gardening waste management methods in EI, aiming to find publications in the Scopus and Google Scholar databases, using a personalized search string. A total of 14 documents were obtained and included in the study, meeting all the criteria. These documents were listed according to the methods of quantification and disposal of garden waste already existing for EI. The leading topic about the disposal of this type of waste in EI is composting. The methods of total weighing and volume definition were the leading topic for quantification. The study collaborates with sustainability practice within the EI, revealing sustainable alternatives of green waste management.